Medicare Spending for Breast, Prostate, Lung, and Colorectal Cancer Patients in the Year of Diagnosis and Year of Death. (26th July 2017) - Chen, Christopher T.; Li, Ling; Brooks, Gabriel; Hassett, Michael; Schrag, Deborah
Abstract : Objective: To characterize spending patterns for Medicare patients with incident breast, prostate, lung, and colorectal cancer. Data Sources/Study Setting/Study Design: 2007–2012 data from the Surveillance, Epidemiology, and End Results Program linked with Medicare fee‐for‐service claims. Data Collection/Extraction Methods: We calculate per‐patient monthly and yearly mean and median expenditures, by cancer type, stage at diagnosis, and spending category, over the years of diagnosis and death. Principal Findings: Over the year of diagnosis, mean spending was $35, 849, $26, 295, $55, 597, and $63, 063 for breast, prostate, lung, and colorectal cancer, respectively. Over the year of death, spending was similar across different cancer types and stage at diagnosis. Conclusions: Characterization of Medicare spending according to clinically meaningful categories may assist development of oncology alternative payment models and cost‐effectiveness models.